Protonating metal-metal bonds: Changing the metal-metal interaction from bonding, to nonbonding, and to antibonding. (15th January 2022) - Yang, Xin; Chin, Robert M.; Hall, Michael B.
Graphical abstract: Density functional theory has been used to determine the geometric and electronic structure of the series of ruthenium dimers as they are protonated. Complete analysis of the bonding is provided by molecular orbital interactions, quantum theory of atoms in molecules and natural bond orbitals. Abstract: Density functional theory (DFT) has been used to determine the geometric and electronic structure of the series [cis-{(η 5 -C5 H3 )2 (CMe2 )2 }-Ru2 (CO)4 (μ-H)n ] n + (n = 0, 1, 2) and their di-tert-butyl-bipyridine (bipy) analogs ((CO)2  = bipy). The results have been analyzed by using natural bond orbitals (NBO) and quantum theory of atoms in molecules (QTAIM). This series provide a thorough description of the changes in the bonding that occur as the Ru-Ru bond in the n = 0 complexes is first protonated to form the 18-electron hydrogen bridged complexes, which each has a 3-center/2-electron Ru-H-Ru bond but not a direct Ru-Ru bond, and then protonated again to form dibridged complexes, which have two 3-center/2-electron Ru-H-Ru bonds and even without a direct Ru-Ru bond have an electron count of 19 electrons, which is compensated by having one more antibonding than bonding Ru-Ru molecular orbitals.